TRANSFORMASI KEWIRAUSAHAAN DI ERA DIGITAL: SINERGI BRANDING, MARKETING, DAN KAPABILITAS DIGITAL PELAKU USAHA - Ummul Khaeri; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Entrepreneurial transformation in the digital era is driven not only by technological advancement but also by entrepreneurs’ ability to systematically integrate branding strategies, digital marketing, and digital capabilities. This article examines the interrelationship among these three components through a reflective integrative conceptual analysis using scholarly literature published between 2020 and 2025. The synthesis reveals that digital branding serves as the foundation for creating value, identity, and consumer trust within increasingly competitive markets. Digital marketing operates as the primary mechanism for delivering value through personalized, data-driven, and responsive interactions. Meanwhile, digital capability emerges as a critical enabling factor that determines the effectiveness of both branding and marketing efforts, particularly in leveraging technology, utilizing data analytics, and adapting to digital platforms. A key finding of this study is that branding, marketing, and digital capabilities form a mutually reinforcing system that collectively drives entrepreneurial transformation. Entrepreneurs who successfully align brand identity, marketing strategies, and technological competence demonstrate greater adaptability to shifts in consumer behavior and the evolving structure of digital markets. This article provides a theoretical contribution by offering an integrative perspective that broadens the understanding of digital entrepreneurship as a strategic, rather than purely technological, phenomenon. Nevertheless, the proposed conceptual framework requires further empirical validation to capture contextual variations across sectors and business scales..